Traditional Malay Games as Ethnomathematics: Strengthening Mathematical Ability and Nationalism in Elementary School Students - Nina Zakiah; Syarifah Ivonesti (Educazione: Journal of Education and Learning, 2025)
The persistently low mathematical ability and weakening sense of nationalism among elementary school students underscore the need for contextual, culturally responsive learning innovations. This study analyses the effect of implementing ethnomathematics through traditional Malay games on students' mathematical ability and nationalism. A quantitative approach with a quasi-experimental, nonequivalent control group pretest-posttest design was employed. The participants were 40 elementary school students from SD IT Alfatih, Bengkalis, divided into an experimental group and a control group. Data were collected through a mathematics achievement test and a nationalism questionnaire, then analyzed using descriptive statistics and Multivariate Analysis of Variance (MANOVA). The results revealed a significant multivariate effect of ethnomathematics-based learning through traditional Malay games on mathematical ability and nationalism simultaneously (Wilks' Lambda = 0.216; p < 0.001). Follow-up univariate analyses confirmed significant effects on mathematical ability (F = 120.773; p < 0.001) and nationalism (F = 24.374; p < 0.001), with the experimental group attaining substantially higher posttest scores. These findings indicate that integrating traditional Malay games into mathematics learning enhances mathematical competence while strengthening nationalism, demonstrating the potential of ethnomathematics to unite cognitive and affective outcomes within a single culturally grounded framework.